Evaluating the Impact of Public Student Subsidies on Low-Cost Private Schools in Pakistan - Barrera-Osorio, Felipe (Taylor and Francis, 2015)
This paper examines the impacts of accountability-based public per-student subsidies provided to low-cost private schools in Punjab, Pakistan on student enrolment and school inputs. Programme entry is contingent on achieving a minimum pass rate on a specially-designed academic test. We use regression discontinuity to estimate impacts on schools that joined the programme in the last entry round (phase 4) before follow-up survey data collection. We find large positive impacts on school enrolment, number of teachers, and other inputs for programme schools near the minimum pass rate.